Simple approach for analysis of beam-column elements on homogeneous and non-homogeneous elastic soil. (15th October 2020) - Vega-Posada, Carlos A.; Gallant, Aaron P.; Areiza-Hurtado, Mauricio
Highlights: Beam-column elements with generalized end-boundary conditions in Pasternak soil. Differential Transformation Method (DTM) applied to solve the governing equation. Flexibility to incorporate semirigid connections and lateral restraints. Comparison with other methods to highlight accuracy and implementation. Abstract: A simplified analytical approach to analyze soil-structure interaction of beam-column elements (i.e., beams, columns, piles, etc.) with generalized end-boundary conditions on a homogeneous or non-homogeneous Pasternak foundation is developed. The Differential Transformation Method (DTM) is employed to solve the equation that governs the mechanical response of the proposed beam-column element. Using the same set of expressions, the proposed formulation can be used to conduct both static and stability analyses. It also provides the flexibility to incorporate the effects of semirigid connections, lateral restraints, and axial and lateral load at the ends of the element. The effects of any slenderness ratio and element/soil stiffness ratio are captured with the proposed formulation. Five examples are examined to illustrate the simplicity of the method to conduct static and stability analyses. The proposed method is compared with more rigorous, but cumbersome, methods to highlight the accuracy and relative ease of implementation.